PENERAPAN TERAPI RANGE OF MOTION (ROM) UNTUK MENINGKATKAN KEKUATAN OTOT PADA ANGGOTA KELUARGA DENGAN POST STROKE DI WILAYAH KERJA UPTD PUSKESMAS PLERED - Yuli Erlina; Dina Hartini; Sinta Safitri (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Every year there are 13.7 million new cases of stroke that occur in the world. In Indonesia (2018), the population aged ≥ 15 years was 10.9% or an estimated 2,120,362 people who had a stroke. West Java Province has a stroke prevalence of 11.4%, or an estimated 131,846 people. Post Stroke is a medical emergency that has occurred due to sudden poor blood flow to the brain which causes death of brain tissue, so that the function of controlling body movements controlled by the brain does not function. The aim of this application is to increase muscle strength with Range Of Motion (ROM) therapeutic intervention. Range Of Motion (ROM) is a programmed exercise to move body parts to improve muscle strength levels. This research method is descriptive in the form of an evidence-based case study with Mr.D as a sample. The results of the application show that the value of the muscle strength of the right upper limb and right lower limb of Tn.D before being given 2/3 intervention, and after being given the Range of Motion (ROM) therapeutic intervention for 10 days was 33,3% for the right upper limb and 16,6% for the right lower limb, so that the value of the muscle strength of the right upper limb and right lower limb becomes 4/4. It is hoped that the patient's family can independently apply Range Of Motion (ROM) to help increase the patient's muscle strength